Cytotoxic and Antioxidant Effects of Antimalarial Herbal Mixtures - Isaac Dadzie; Shaibu Adams Avorgbedo; Regina Appiah-Opong; Obed Cudjoe (International Journal of Microbiology)
Many developing countries depend on herbal mixtures as the first line and cost-effective therapy for malaria. These mixtures with such curative tendencies may also be a source of toxicity to host cells. On the other hand, these mixtures may have anticancer potential activity characterized by cytotoxicity to cancer cells. The aim of the study was to determine the cytotoxic and antioxidant effects of five different antimalarial herbal mixtures. Five antimalarial herbal mixtures commonly used in Ghana (coded as STF, SMH, SMM, SGM, and STT) were purchased and freeze-dried. The dried samples were tested on human acute T-cell leukemia (Jurkat) and breast adenocarcinoma (MCF-7) cell lines. Cytotoxicity was assessed using the tetrazolium-based colorimetric (MTT) assay while antioxidant activity was determined using DPPH free-radical scavenging assay. Among the mixtures, SMM and SGM exhibited the strongest cytotoxicity towards Jurkat cells (IC50 values 59.17 μg/ml and 49.57 μg/ml, respectively), whereas STT showed the weakest cytotoxicity (IC50 = 244.94 μg/ml). Cytotoxic effect of SMM was also strongest towards MCF-7 cells whilst the least cytotoxic sample was SGM (IC50 > 1000 μg/ml). SMM had the highest antioxidant percentage (EC50 = 1.05 mg/ml). The increasing order of antioxidant percentage among the five herbal mixtures is SMM > SMH > STT > STF > SGM. The herbal mixtures may be potential sources of toxic agents to host cells. Therefore, further toxicity studies must be performed to safeguard health of the public. Interestingly, cytotoxicities exhibited by SMM and SGM suggest the presence of anticancer constituents in them which warrant further studies.